High effort, low reward, and cardiovascular risk factors in employed Swedish men and women: baseline results from the WOLF Study. Issue 9 (September 1998) - Peter, R; Alfredsson, L; Hammar, N; Siegrist, J; Theorell, T; Westerholm, P
Abstract : STUDY OBJECTIVE: To examine associations between measures of work stress (that is, the combination of high effort and low reward) and cardiovascular risk factors. DESIGN: Cross sectional first screening of a prospective cohort study. SETTING AND PARTICIPANTS: The study was conducted among 5720 healthy employed men and women living in the greater Stockholm area aged 19-70 years. All analyses were restricted to subjects with complete data (n = 4958). The investigation of associations between indicators of effort-reward imbalance and cardiovascular risk factors was restricted to the age group 30-55 years (n = 3427). MAIN RESULTS: Subjects reporting high effort and low reward at work had a higher prevalence of well known risk factors for coronary heart disease. After adjustment for relevant confounders, associations between a measure of extrinsic effort and reward (the effort-reward ratio) and hypertension (multivariate prevalence odds ratio (POR) 1.62-1.68), increased total cholesterol (upper tertile 220 mg/dl)(POR = 1.24) and the total cholesterol/high density lipoprotein(HDL)-cholesterol ratio (upper tertile 4.61)(POR 1.26-1.30) were found among men. Among women a measure of high intrinsic effort (immersion) was related to increased low density lipoprotein (LDL)-cholesterol (upper tertile 130 mg/dl)(POR 1.37-1.39). Analyses of variance showed increasing mean values of LDL cholesterol with an increasing degree of the effort-reward ratio among men and increased LDL-cholesterol among women with high levels of intrinsic effort (upper tertile of immersion). CONCLUSIONS: Findings lend support to the hypothesis that effort-reward imbalance represents a specific constellation of stressful experience at work related to cardiovascular risk. The relation was not explained by relevant confounders (for example, lack of physical exercise, body weight, cigarette smoking).